Anharmonic Oscillators with Infinitely Many Real Eigenvalues and PT-Symmetry - Shin, K.C. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We study the eigenvalue problem −u''+V(z)u=λu in the complex plane with the boundary condition that u(z) decays to zero as z tends to infinity along the two rays arg z=−π/2± 2π/(m+2), where V(z)=−(iz)m−P(iz) for complex-valued polynomials P of degree at most m−1≥2. We provide an asymptotic formula for eigenvalues and a necessary and sufficient condition for the anharmonic oscillator to have infinitely many real eigenvalues.